Feminilidade em Freud e na contemporaneidade repercuções e impasses - Valença, Maria da Conceição Araújo (2003)
This work analyzes, according to Freudian texts, the route to become a woman , its contributions and impasses today. It s in the encounter with the feminine, attempting to understand the meaning of fantasies and hysterical symptoms, that Freud found out the inconsciousness, the trauma, sex, that drove to childhood sexual experiences. Studying sexuality in perversion, we face childhood sexuality and its many-formed perverted nature. Sexuality leaves then, perversion field to come into impulse and desire field. In this context, Freud develops a theory of feminine sexuality referred to castration and phallic primacy, only way to the acquisition of a normal feminism. Reflecting and analyzing to become a woman according to Freud, sent it to the society of spectacle and narcissism worship. Woman, through this path, has conquered many spaces, creating new social links: has left private space, meant by marriage and motherhood, to be at the spectacle scenery. Viewing this scenery in the consumers´ universe society and its consequences in the feminine subjectivity, tending to analyze in details woman s relation with her own body and sexuality, stressed by sexual excess and tied to an ideal body, source of sorrow and pain. At present-day, that s the image of woman-body-sex that comes up with masks and technological devices, searching the desired-perfect body, trying to deceive failure incompleteness, death. It s body-sex as object of desire and consumption, that sells anything and becomes other s object of pleasure. It shows an open-wide sexuality, primitive, without limits. It changes from a hysterical to a body-sex woman, the one that plays the whore in the masculine fantasy, legitimated by the social, idealized and feminine model. Feminism meaning what the seduction and erotism game owns as the most sublime, mysterious and gorgeous-showed in a subtle erotic gesture, a neckline,a revelation has no value today. The woman shows, through her highly erotized body, the necessity of searching other knowledge s, before new forms of erotization she faces